2011
DOI: 10.1371/journal.pone.0021075
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Linkage to Injected Tissues Is a Distinctive Property of Oxidized Avidin

Abstract: We recently reported that the oxidized avidin, named AvidinOX®, resides for weeks within injected tissues as a consequence of the formation of Schiff's bases between its aldehyde groups and tissue protein amino groups. We also showed, in a mouse pre-clinical model, the usefulness of AvidinOX for the delivery of radiolabeled biotin to inoperable tumors. Taking into account that AvidinOX is the first oxidized glycoprotein known to chemically link to injected tissues, we tested in the mouse a panel of additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…There is a need to develop local treatments for cancer lesions that are derived from or reside within tissues/organs that are very different in terms of stromal composition, vascularization, density and other features. AvidinOX has been previously shown to form Schiff's bases with proteins in a variety of tissues and in several animal species (7)(8)(9)(10)(11)(12)(13). Long tissue residence of AvidinOX is also currently being confirmed in human patients with liver metastases and other inoperable tumor lesions as indicated by selective and consistent uptake of intravenous 177 Lu-ST2210 administered 1 and up to 15 days after intra-tumor AvidinOX (ClinicalTrials.gov NCT02053324 and NCT03188328, data not shown).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There is a need to develop local treatments for cancer lesions that are derived from or reside within tissues/organs that are very different in terms of stromal composition, vascularization, density and other features. AvidinOX has been previously shown to form Schiff's bases with proteins in a variety of tissues and in several animal species (7)(8)(9)(10)(11)(12)(13). Long tissue residence of AvidinOX is also currently being confirmed in human patients with liver metastases and other inoperable tumor lesions as indicated by selective and consistent uptake of intravenous 177 Lu-ST2210 administered 1 and up to 15 days after intra-tumor AvidinOX (ClinicalTrials.gov NCT02053324 and NCT03188328, data not shown).…”
Section: Discussionmentioning
confidence: 96%
“…We recently described a novel method that allows suboptimal doses of biotinylated agents to become effective therapies in models of HNC. The treatment is based on the intra-tumor injection of AvidinOX, an oxidized avidin derivative that exhibits the distinctive property of forming Schiff's bases with tissue proteins (7)(8)(9)(10)(11), followed by systemically administered radioactive biotin (12) or biotinylated cetuximab (bCet) (13). In the present study, we show that the injection of AvidinOX into FaDu pharynx squamous cell carcinoma cells xenografted in the mouse tongue increases the anti-tumor activity of a suboptimal bCet dose administered intraperitoneally after 24 h. The data also indicate that the treatment can be repeated at least twice, 1 week apart, and that the therapeutic efficacy could be further improved by including a low dose of cisplatin in the protocol.…”
Section: Introductionmentioning
confidence: 99%
“…62 Attempts to uniquely improve trastuzumab efficacy are also coming from our group at Alfasigma SpA. From our long experience in tumor pre-targeting based on the exploitation of the avidin-biotin interaction, [63][64][65][66][67][68][69] we recently found that by anchoring biotinylated trastuzumab or pertuzumab to AvidinOX (modified avidin chemically reacting with tissue proteins)-treated tumor cells, antibody reactivity is increased by several orders of magnitude. 70 This peculiar phenomenon, which is related to the inhibition of the targeted receptor trafficking, could allow significant reduction of antibody doses with consequent reduction of toxicity and costs.…”
Section: New Products/new Mechanisms Of Actionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] Designing an efficient carrier is generally required for drug delivery or artificial regulation of cellular functions. [21][22][23][24][25][26][27][28][29][30] Because the mammalian living cell surface is rich in anionic sulfated proteoglycans, a cationic carrier is efficiently adsorbed on the cellular surface, and then efficiently internalized through an endocytosis-like pathway. This adsorption-mediated endocytosis is nonspecific to cell type, but sufficient amount of carrier can be internalized uniformly into cells in culture.…”
Section: Introductionmentioning
confidence: 99%
“…Highly cationic nature of avidin is advantageous for intracellular delivery of biotinylated protein, nucleic acids, or macromolecules 13‐20 . Designing an efficient carrier is generally required for drug delivery or artificial regulation of cellular functions 21‐30 . Because the mammalian living cell surface is rich in anionic sulfated proteoglycans, a cationic carrier is efficiently adsorbed on the cellular surface, and then efficiently internalized through an endocytosis‐like pathway.…”
Section: Introductionmentioning
confidence: 99%